On the Potential Environmental Repercussions of Hydroelectricity: A Contribution Based on Life Cycle Assessment of Ecuadorian Hydropower Plants - Lazo Vásquez, David (2022)
The share of world energy consumption for electricity generation by source is primarily based on coal and natural gas. Within the last years, governments have implemented policies to promote investment in renewable energy. In Ecuador, the share of hydroelectricity has rapidly increased without regarding long-term environmental impacts. This paper aims to develop a cradle-to-gate life cycle assessment of two representative plants of Ecuador (Agoyán and Paute, with 156 MW and 1075 MW of installed capacity, respectively). The life cycle inventory contains the primary flows of energy and matter during the construction, operation, and final disposal stages, with 1 kWh as a functional unit. The life cycle impact assessment uses the CML 2000 midpoint potential categories, including Abiotic Depletion, Acidification, Eutrophication, and Global Warming. The construction stage is the leading contributor to the global impacts, and the dam the environmental hot spot of both plants, and the reservoir flooding represents the major contributor to the impact during the operation stage. Furthermore, electricity generation in plants with a larger scale can lead to fewer impacts, suggesting that constructing large-scale plants can reduce the global impacts in countries with similar hydropower potential. This methodological framework serves as a decision-making criterion for evaluating the environmental performance of other renewable energy systems.